Angiotensin converting enzyme gene deletion allele is independently and strongly associated with coronary atherosclerosis and myocardial infarction. Issue 6 (December 1995) - Arbustini, E.; Grasso, M.; Fasani, R.; Klersy, C.; Diegoli, M.; Porcu, E.; Banchieri, N.; Fortina, P.; Danesino, C.; Specchia, G.
Abstract : OBJECTIVE–To investigate the association of the three angiotensin converting enzyme (ACE) genotypes, DD, ID, and II, with the occurrence or absence of coronary atherosclerosis and with myocardial infarction and hypertension. DESIGN–Cohort analysis study. SETTING–North-Italy reference centre. SUBJECTS–388 white Italian patients (281 males; mean age 60.7 (SD 12.5) years) with proven coronary atherosclerosis (n = 255) or with angiographically normal coronary arteries (n = 133). A further group of 290 healthy blood donors was tested for allele frequency comparison. INTERVENTIONS–ACE/ID polymorphism was analysed with polymerase chain reaction on DNA from white blood cells. MAIN OUTCOME MEASURES–Coronary atherosclerosis, myocardial infarction, hypertension. RESULTS–The D and I allele frequencies were respectively 0.63 and 0.37 in the overall healthy blood donor group and 0.66 and 0.34 in the overall study group. In the latter, univariate analysis showed (1) that coronary atherosclerosis (255 patients) was associated with the deletion allele, with an odds ratio (OR) of 5.78 for DD/II, P < 0.001, and 2.39 for ID/II, P = 0.006; and (2) that myocardial infarction (154 patients) was associated with the DD genotype (OR DD/II = 2.56, P = 0.007), but not with the ID genotype (OR DD/II = 1.96, P = 0.056). Finally, hypertension proved to be unrelated with the ACE genotype. The distribution between the three genotypes of known risk factors for coronary artery disease was similar. Logistic regression modelling, performed to test the association of the selected risk factors simultaneously with coronary atherosclerosis and myocardial infarction, showed that the deletion allele (whether DD or ID) was the strongest risk factor for atherosclerosis, and that the D allele was significantly associated with the risk of infarction (although to a lesser extent than with coronary atherosclerosis). CONCLUSION–ACE deletion polymorphism is strongly and independently associated with coronary atherosclerosis and, to a lesser extent, with myocardial infarction. As such, the results are analogous to what has already been reported in French white, Japanese, and Welsh coronary patients.